2022
DOI: 10.1093/ejcts/ezac264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative atrial fibrillation on early and mid-term outcomes of coronary artery bypass graft surgery

Abstract: Objectives The long-term prognostic role of postoperative atrial fibrillation (POAF) on cardiovascular outcomes in patients undergoing cardiac surgery is uncertain. We aimed to investigate the impact of new-onset POAF on mid-term adverse cardiovascular events after coronary artery bypass graft (CABG) surgery. Methods This was a retrospective cohort study of patients who underwent isolated CABG without a preoperative history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…POAF is the common complication in patients following CABG. It has been reported that POAF is associated with an increased risk of poor prognosis ( 3 ). It is important to identify risk factors of POAF in order to better prevent POAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POAF is the common complication in patients following CABG. It has been reported that POAF is associated with an increased risk of poor prognosis ( 3 ). It is important to identify risk factors of POAF in order to better prevent POAF.…”
Section: Discussionmentioning
confidence: 99%
“…New-onset atrial fibrillation (AF) is the most common complications after coronary artery bypass graft (CABG) with a reported incidence of 20–40% ( 1 ). Post-operative AF (POAF) is associated with increased stroke, life-threatening ventricular arrhythmia, mortality and health-care costs ( 2 , 3 ). It is important to identify patients at high risk of developing AF following surgical coronary revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…However, with an aging population needing heart surgery, there is a greater need for a better knowledge of the impact on patient outcomes, medical facilities, and healthcare costs. Previous research has linked POAF following CABG with both early and late mortality (4). Age is a significant predictor of POAF, which also correlates with early and late mortality following CABG (5).…”
Section: Introductionmentioning
confidence: 96%
“…The incidence of POAF in isolated coronary artery bypass grafting (CABG) ranges from 13–33% ( 1 - 5 ). In patients undergoing isolated off-pump coronary artery bypass grafting (OPCABG), the incidence of POAF ranges from 8–20% ( 1 , 2 , 6 - 8 ).…”
mentioning
confidence: 99%
“…These include older age, renal failure, impaired left ventricular ejection fraction, diabetes mellitus, chronic obstructive pulmonary disease, use of cardiopulmonary bypass and left atrial size ( 1 , 5 , 6 , 10 , 11 ). Although POAF after cardiac surgery was historically thought to be benign and self-limiting, several studies have now shown that it is associated with a substantial risk for adverse outcomes, including increase in both early and late mortality, morbidities such as postoperative stroke, congestive heart failure, gastrointestinal dysfunction as well as increased length of hospitalization and healthcare costs ( 2 , 12 - 14 ). Considerable efforts have been directed towards the prevention of POAF, mainly focusing on pharmacological agents.…”
mentioning
confidence: 99%